2015
DOI: 10.1111/nmo.12700
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant ability of the Eating Assessment Tool‐10 to detect aspiration in individuals with amyotrophic lateral sclerosis

Abstract: Background Oropharyngeal dysphagia is prevalent in individuals with amyotrophic lateral sclerosis (ALS) leading to malnutrition, aspiration pneumonia and death. These factors necessitate early detection of at risk patients to prolong maintenance of safe oral intake and pulmonary function. This study aimed to evaluate the discriminant ability of the Eating Assessment Tool (EAT-10) to identify ALS patients with unsafe airway protection during swallowing. Methods 70 ALS patients completed the EAT-10 survey and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 27 publications
(43 reference statements)
1
64
1
13
Order By: Relevance
“…20 The EAT-10 was reported as a discriminative tool for identification of aspiration risk in 2 previous studies. 2,13,14 Our findings regarding high discriminant ability of the T-EAT-10 in detecting aspiration in neurological patients are similar to the findings of these studies. 2,13,14 Different criterion scores were used due to methodological differences in these studies.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…20 The EAT-10 was reported as a discriminative tool for identification of aspiration risk in 2 previous studies. 2,13,14 Our findings regarding high discriminant ability of the T-EAT-10 in detecting aspiration in neurological patients are similar to the findings of these studies. 2,13,14 Different criterion scores were used due to methodological differences in these studies.…”
Section: Discussionsupporting
confidence: 82%
“…The earlier investigation used a cut value of 8, and reported that this score correctly identified 85.7% of ALS aspirators with 71.9% specificity. 2 The cut score according to the mean EAT-10 of non-aspirators in the study of Cheney et al 13 was 16 as our cut score from our neurological patient population. Cheney et al 13 reported that the sensitivity of EAT-10 was 71.0%, the specificity was 53.0%, and the negative predictive value was 89.0%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations